2007
DOI: 10.1124/jpet.107.121699
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of 5-Aza-2′-Deoxycytidine on Spermatogenesis Include Reduced Sperm Function and Selective Inhibition of de Novo DNA Methylation

Abstract: The anticancer agent, 5-aza-2Ј-deoxycytidine (5-azaCdR, decitabine), causes DNA hypomethylation and a robust, dosedependent disruption of spermatogenesis. Previously, we have shown that altered testicular histology and reduced sperm production in 5-azaCdR-treated animals is associated with decreased global sperm DNA methylation and an increase in infertility and/or a decreased ability to support preimplantation embryonic development. The goal of this study was to determine potential contributors to 5-azaCdR-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…No formal carcinogenicity studies were conducted as part of the decitabine development program on the basis of its intended clinical use as an anticancerdrug for treatment ofolder patients with AML who have limited life expectancy; however, evidence from the literature indicates that decitabine has carcinogenic potential. Available data also indicate that decitabine has adverse effects on all aspects of the reproductive cycle, including fertility, embryo-fetal development, and postnatal development [36][37][38][39]. Most toxicities observed from treatment with decitabine are likely to be related to the cytoxicity of the molecule.…”
Section: Nonclinical Aspects and Clinical Pharmacologymentioning
confidence: 99%
“…No formal carcinogenicity studies were conducted as part of the decitabine development program on the basis of its intended clinical use as an anticancerdrug for treatment ofolder patients with AML who have limited life expectancy; however, evidence from the literature indicates that decitabine has carcinogenic potential. Available data also indicate that decitabine has adverse effects on all aspects of the reproductive cycle, including fertility, embryo-fetal development, and postnatal development [36][37][38][39]. Most toxicities observed from treatment with decitabine are likely to be related to the cytoxicity of the molecule.…”
Section: Nonclinical Aspects and Clinical Pharmacologymentioning
confidence: 99%
“…The authors suggested that each of the regions present a different vulnerability to present alterations in function of the degree of tandem repetitions that they contain. In mice, different studies have demonstrated that anomalies of the genes that codify for DNMT [32][33][34][35][36][37] or variations in the functionality of these proteins due to interaction with environmental factors 10,[38][39][40] produce methylation alterations in regions regulated by genetic imprinting, causing infertile phenotypes.…”
Section: -mentioning
confidence: 99%
“…During spermatogenesis the genome undergoes massive epigenetic modifications which are crucial for fertilization and embryogenesis [11,17,30]. Early primordial germ cells (PGCs) possess a somatic-like methylation pattern with a high degree of genome-wide DNA methylation.…”
Section: Introductionmentioning
confidence: 99%